Quality of Reporting of Nursing and Midwifery Cohort Studies According to the STROBE Statement - Abbas Heydari; Abdolghader Assarroudi (Tehran University of Medical Sciences, 2014)
Background & Aim: Transparent and appropriate reporting of studies facilitates critical appraisal, application and combination of findings. The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement, is a relatively new statement in order to improve the quality of reporting of observational studies. The present study aimed to assess the quality of reporting nursing and midwifery cohort studies according to the STROBE statement published in the Iranian electronic databases .   Methods & Materials: In this cross-sectional study, we conducted a literature search in the SID, Magiran, Irandoc, Iranmedex databases and Google Scholar using the "cohort" keyword. It produced 1951 articles. After excluding duplicates and irrelevant articles, 241 papers were remained. We included: papers that were published after publishing of the STROBE statement, papers with cohort designs, and papers which their first author or corresponding author were nurse or midwife. Finally, we included 33 papers in our study. We evaluated the papers with the extended STROBE statement. Data were analyzed using the Kruskal Wallis, Mann Whitney and Spearman tests .   Results: About half (48.5%) of the papers had a prospective design; others were historical cohort. The compliance with the STROBE statement was 56%. The title, abstract and introductions had generally good quality. The missing data, loss to follow-up and sensitivity analyses had poor quality. There were no associations between the papers' reporting quality with the year of publications, authors' specialty, design of the study, and the time of reviewing process .   Conclusion: The quality of reporting in nursing and midwifery cohort studies was moderate. Reporting the essential elements of cohort studies according to the STROBE statement is recommended .